Hybrid membrane systems for water purification technology, systems design and operation - Singh, Rajindar, 1947-
Written in a practical style, this comprehensive book emphasizes on process description, key unit operations, plant equipment description, equipment installation, safety and maintenance, process control, plant start-up, operation and troubleshooting. It is supplemented by case studies and useful engineering rules-of-thumb.